Ian Stevenson’s Rabih Elawar at 60: Past-Life Memory Loss and Retention in Adulthood - Matlock, James G.; Hatoum, Khattar; Louie, Carole (Journal of Anomalous Experience and Cognition, 2026)
Objective: We wanted to assess how well a Lebanese Druze man, Rabih Elawar, now living in Richmond, Virginia, retained the past-life memories studied by Ian Stevenson when he was a child in Lebanon. Methods: Over a series of interviews, we first asked Rabih to relate all he recalled about the previous life, then presented Stevenson’s report, which he had not previously read, to get his responses to items he had not mentioned spontaneously. Results: Statements Stevenson recorded in his published report and unpublished field notes and memories Rabih recounted to us are highly consistent, although Rabih recalled some events differently and related details Stevenson apparently did not hear about. When we presented the items recorded by Stevenson but not mentioned spontaneously by him, Rabih was prompted to recall these also and clarified points on which there was apparent disagreement. Conclusions: Rabih’s recall of the previous life at 58-60 is superior to what has been reported for past-life memory retention among other Lebanese Druze adults or with Sri Lankan, Indian, Brazilian, and American adults. This may be related to Rabih’s recalling a life in the same village and same extended family that, moreover, ended only a short while (6 months) before his birth, providing plentiful cues to recall from early in his life. Our findings are consistent with those regarding present-life memory retention and loss, supporting the view that the foundations of past-life memory are closely similar to those of present-life memory.